The Influence of School Culture on the Character of Junior High School Students - Widya Wanti, Maria; Darmawan, Didit (Journal of Islamic Elementary Education, 2024)
This study aims to explore the influence of school culture on character development among students at the Junior High School (SMP) level. School culture encompasses the values, norms, and practices that develop within the educational environment, which can significantly affect students' behavior, attitudes, and social interactions. In the context of education, student character is crucial as it plays a vital role in shaping their personality and ethics for the future. The methodology employed in this research is a quantitative approach using surveys as the data collection tool. The respondents consist of students and teachers from several randomly selected SMPs in a specific region. The data collected are analyzed using statistical techniques to identify the relationship between school culture and student character. The results indicate that a positive school culture, characterized by cooperation, discipline, and recognition of achievements, significantly contributes to the development of student character. Students exposed to a supportive school culture tend to exhibit higher levels of integrity, empathy, and responsibility compared to those in less supportive environments. These findings highlight the importance of creating a positive and inclusive school culture in efforts to foster good student character. Therefore, school administrators, educators, and other educational stakeholders are encouraged to design and implement programs that strengthen school culture. This research is expected to serve as a reference for developing educational policies focused on character development, ultimately leading to the creation of a more qualified, ethical, and prepared generation to face future challenges.